Exploration of factors of digital photo hoarding behavior among university students and the mediating role of emotional attachment and fear of missing out - Yu, Wenjing; Chang, Xueqin (Frontiers in Psychology, 2025)
With the widespread use of digital technology and devices, college students are prone to hoarding digital photos. Based on the SOR model, this study conducted a survey of 294 college students and used partial least squares structural equation modeling (PLS-SEM) to study the factors of digital photo hoarding among college students, as well as the mediating effects of emotional attachment and fear of missing on the relationship between various factors and digital photo hoarding behavior. The results revealed that emotional attachment, fear of missing out, interpersonal influence, life demand, and technological progress are important influencing factors for college students' digital photo hoarding behavior. In addition, Emotional attachment mediates the relationship between emotional needs, interpersonal influence, and technological progress with digital photo hoarding behaviors. Fear of missing out mediates the association between emotional needs, interpersonal influence, and technological progress, and digital photo hoarding behavior. Finally, we discuss the implication, limitations, and directions for future research and conclusion of this work.